Penguatan Variasi Produk Melalui Penerapan Teknologi Tepat Guna Pada Kampung Lemon Desa Eduwisata Sumberdem - Siti Ulfatul Faizah; Tisa Reta Vianda; Agung Winarno; Wening Patmi Rahayu (Rengganis Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to increase the business capacity of Kampung Lemon by strengthening marketing, product innovation, branding, and financial management. The main challenges faced include conventional marketing, limited product innovation, the lack of a visual product identity, and a manual financial recording system. The method used in this program is direct mentoring through training and practice for business owners. Activities include creating and managing digital marketing accounts through e-commerce platforms and social media, developing the "Lempah" liquid lemon product for increased shelf life, creating a logo as a product identity, and developing a simple Microsoft Excel-based bookkeeping template. The results of this activity indicate an increase in digital marketing capabilities, marked by increased market reach, improved quality of the liquid lemon product for better marketability, the creation of a more professional product visual identity, and a more organized and systematic financial recording system. This program has had a positive impact on the development of Kampung Lemon and is the first step in supporting business sustainability through the implementation of technology and improved management.